[Rocks in Grotto at Heimaey] - Streng, Evelyn Fiedler (1975)
Photograph of rocks from a grotto along Heimaey. Pointed, dark rocks peek out of the grey ocean water at the center and left side of the photograph. A flat, grass covered platform is visible to the right beside a mountain structure behind it. A dark rock arch structure sits in the top right corner of the photograph. Grey clouds cover the sky in the background.